Game and Gamification: Educational Innovation in a Society in Continuous Change - Gil Quintana, Javier (2019)
In this essay, we have tried to make an approximation to the concept of game and gamification since it is an innovative proposal that is currently being used in educational practices whose teachers are incorporating experiences of gamification in their classrooms. Based on the different authors that throughout history have reflected and concentrated on the role of education which started from the pedagogical methods of the new, current school of thought, we support its premise on the importance of implementing game in learning, also confirming a wide range of advantages that gamification and its integration in digital learning currently have, making it possible to increase the participation of students in the collective construction of knowledge, the projection of its interaction in the classroom, a greater motivation towards learning, and a more enriching and fun environment in the classroom and its experiences with the aim of engaging in the achievement and exceeding of the curricular lines set for their corresponding age and level.